Síntese e caracterização de complexos de fórmula geral [Ru(AA)(P-P)(N-N)]PF6, onde (AA= aminoácidos; PP=bifosfinas; N-N= 2,2 -bipiridina e derivados e 1,10-fenantrolina): avaliação de suas potencialidades citotóxicas - Santos, Edjane Rocha dos (Universidade Federal de São Carlos, 2011)
The present work describes the syntheses and characterization of complexes of general formula [Ru(AA)(P-P)(N-N)]PF6 where AA = aminoacids (Gly, Ala, Val, Met, Tyr, Trp, Leu, Arg, Ser, Lys, His); P-P = 1,4- bis(diphenylphosphino)butane and 1,3-bis(diphenylphosphino)propane; N-N= 1,10- phenanthroline, 4,4 -dimethyl-2,2 -bipyridine, 5,5 -dimethyl-2,2 -bipyridine e 4,4 - methoxy-2-2'-bipy. The complexes were evaluated against cell lines MDA-MB-231, MCF-7 (breast tumor cells), DU-145 (prostate tumor cells) and in FGH and V79 (fibroblasts, normal cells), HeLa (colon tumor cells), as well as antimicrobial tests (tuberculosis) and antiparasite (malaria (CW-2 chloroquine resistant) and Chagas disease (Y-form) ). By analytical techniques such as elemental analysis, UV-vis and infrared spectroscopies and nuclear magnetic resonance (31P{1H}, 13C{1H} and 1H), it was possible to confirm the proposed structures for the synthesized compounds. By the 31P{1H}, 13C and 1H NMR spectra, it was suggested the presence of isomers, these data combined with the X-ray structure analysis of the [Ru(LLeu)( dppb)(bipy)]PF6, allowed us to conclude that those isomers are diastereoisomers. The cyclic voltammograms of all the complexes are similar with the first anodic wave around 1.1 V being attributed to the oxidation RuII→RuIII, and the second anodic wave, in 1.2 V, is attributed to the oxidation of the COO- group of the aminoacid ligands. In the IR spectra of the complexes, characteristic stretching bands of the group NH2 and COO- were observed, which are found shifted to higher frequencies when compared to the free aminoacid. The complexes here studied presented promising results against diseases evaluated. The values of the IC50 for some of the compounds showed 31,5-fold lower than the cisplatin. The antimycobacterial tests were satisfactory, since the complexes showed lower MIC values than some drugs actually used in the tuberculosis treatment. Considering the antiparasitic tests, low IC50 values were also observed.
Syntheses and characterization of complexes of general formula [Ru(AA)(P-P)(N-N)]PF6, evaluation of their potential cytotoxicity (AA= aminoacids; P-P=biphosphines; N-N= 2,2 -bipyridine and derivatives and 1,10-phenanthroline)
Keywords: Química inorgânica; Complexos de rutênio; Aminoácidos; Química bioinorgânica; Ensaios biológicos; Química medicinal; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA